The effectiveness of the psychosocial empowerment program in early adjustment among adult burn survivors - Evon S. Shokre; Shaymaa Elsayed Mossad Mohammed; Heba Mohammed Mahmoud Elhapashy; Nadia Bassuoni Elsharkawy; Osama Mohamed Elsayed Ramadan; Enas Mahrous Abdelaziz (BMC Nursing, 2024)
Abstract Background Burns constitute a major global health challenge, causing not only physical trauma, but also significant psychosocial and emotional disturbances. The complexity of these injuries requires comprehensive rehabilitation programs that address both the physical and psychosocial aspects of recovery. Despite advances in medical care, there is a lack of standardized, accessible, and sustainable psychosocial interventions for burn survivors, particularly in the transition from hospital to home. This study aimed to develop and evaluate a nurse-led psychosocial empowerment intervention for early adjustment among burn survivors after hospital discharge. Methods The study adopted a quasi-experimental framework. A convenient sample of 80 adult burn survivors was randomly divided into an intervention group, receiving the psychosocial empowerment program, and a control group, continuing standard care from November 2022 to May 2023. The effectiveness of the program was evaluated using various tools that measure satisfaction with appearance, coping abilities, and symptoms of post-traumatic stress disorder (PTSD). The intervention focused on enhancing resilience, self-efficacy, and adaptive coping, through targeted skill building in stress management, adaptability to coping, social reintegration, emotion regulation, and problem-solving. Results Participants in the intervention group demonstrated significant improvements in body image satisfaction, coping abilities, and symptoms of PTSD compared to the control group. Conclusions The psychosocial empowerment program effectively addressed the psychosocial needs of burn survivors and enhanced their early adjustment after hospital discharge. The findings highlight the critical role of psychosocial support in the rehabilitation of burn survivors and underscore the need to integrate such interventions into standard post-discharge care. Future research should focus on the long-term effects of these interventions and their applicability in diverse settings.